Understanding Generation Z at Workplace: The Moderating Role of Mediated Communication between Benevolent Leadership and Organizational Citizenship Behaviors - Andi Juliastri Syafruddin (Universitas Multimedia Nusantara, 2023)
This research focused on the interdisciplinary quest between benevolent leadership, as a contemporary leadership style, and organizational citizenship behaviors (OCBs) through the perspective of communication. The study aimed to examine: first, subordinates’ tendency to show good behaviors towards their peers when prompted by the contemporary leadership style and secondly, it aimed to analyze the influence’s capacity when the interaction between leaders and followers were carried through mediated communication. The research limited its study within the context of Generation Z as subordinates, given their digital nativity, and selected Indonesia as the primary location of investigation. Utilizing a quantitative methodology, a questionnaire was distributed to 210 qualified participants and the collected data was analyzed using a moderated regression analysis on PLS-SEM. The research findings revealed a direct correlation between benevolent leadership and the increase of subordinates’ willingness to take responsibilities outside their contractual duties. Furthermore, the research findings suggested that mediated communication had a stronger influence on OCBs implying the pivotal role of communication in building positive work culture. Despite the result, mediated communications as a moderating variable didn’t give a significant effect on the leaders’ capacity to influence good behavior at the workplace. Overall, this research provided a theoretical framework to understand Generation Z at the workplace and its impact on organizational performance.